Attenuated P. falciparum Parasite Shows Cytokine Variations in Humanized Mice - Zhang, Lei-lei; Li, Jin-Long; Ji, Ming-Xin; Tian, Dan; Wang, Li-Yan; Chen, Chen; Tian, Miao (Frontiers in Immunology, 2020)
A recently developed humanized mouse has been used to assess immune response evoked against the isolated attenuated C9 parasite clone (C9-M; carrying a single insertion disrupting the open reading frame (ORF) of PF3D7_1305500) of Plasmodium falciparum. Significant human RBC engraftment was achieved by ameliorating the residual non-adaptive immune response by clodronate-loaded liposome treatment. Controlled reactive professional phagocytic leukocytes in immnuodeficient mice allowed sizeable human blood chimersism and injected huRBCs act as bona fide host cells for P. falciparum. huRBC-reconstituted immunodeficient mice received infectious challenge with attenuated P. falciparum C9 parasite mutants (C9-M), complemented (C9-C), and wild type (NF54) progenitors to study the role of immune effectors in the clearance of parasite from mouse circulation. C9-M & NF54 parasites grew and developed in the huRBC-reconstituted humanized NSG mice. Further, presence of mutant parasites in deep-seated tissues suggests escape of parasites from host’s immune responses and thus extended survival of parasite. Our results suggest an evasion mechanism that may have been employed by the parasite to survive mouse’s residual non-adaptive immune responses. Collectively, our data suggest that huRBCs reconstituted NSG mice infected with attenuated P. falciparum is a valuable tool to explore the role of C9 mutation in the growth and survival of parasite mutant parasaite and their response to the host’s immune responses. This mouse might help identifying novel chemotherapeutic targets to develop new anti-malarial drugs.